Private Sector Readiness to Contribute to Reconstruction and Recovery in Yemen : Yemen Policy Note 3 - World Bank Group (World Bank, Washington, DC, 2017)
Since 2011, Yemen has suffered a series of crises resulting in the ongoing war which began in March 2015 and which has had major economic consequences. Trade has been badly affected by the war. The Yemeni financial sector faces problems of liquidity, solvency and foreign exchange access. The construction sector is historically an important sector in Yemen and should play a major role in recovery.The Government of Yemen and donors should take immediate steps tosupport the private sector.The year 2011 represented a series of political, social, and economic crises,culminating in the war that started in March 2015, which continue to reverberate throughout Yemen today. Effective reconstruction and recovery demands an understanding of the socio-economic drivers of resilience and recovery in Yemen, including the private sector. The private sector, including micro, small, and medium enterprises (MSMEs) that are prevalent in Yemen, is a major source of employment and provider of basic goods and services, making it an important part of socio-economic resilience and recovery. The capacity oftrade, financial, construction, and agricultural sectors will be of particular importancefor recovery and reconstruction. This note will discuss both conflict related and key systemic constraintson the private sector and priorities for supporting resilience and recovery.It will focus on the private enterprise in sectors that are key to resilience and recovery:trade, construction, finance, and agriculture. It will present immediate and short-term investment and policy recommendationsto support the recovery and stabilization needs of private sector operations during and following the end of the conflict.